INTONATION. THE HISTORY OF INTONATION. THE CONTENT OF INTONATION ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides an in-depth exploration of intonation, its historical development, and its content. It begins with an overview of the evolution of intonation studies, from ancient Greek rhetoric to modern phonetics, highlighting key figures like Aristotle, Otto Jespersen, and Bernard Bloch. The article emphasizes the significance of intonation in distinguishing sentence types, conveying emotions, and managing discourse, showing how intonation patterns affect both meaning and social dynamics. It also discusses the role of intonation in pragmatics, emotional expression, and sentence structure. By breaking down the content of intonation into several components—such as phonemic distinctions, emotional tone, focus, and social signaling—the article illustrates how intonation enriches communication, far beyond simple pitch variation. This piece offers valuable insights into the importance of intonation in language, providing both a historical and functional perspective.